Replication-competent retrovirus vectors for the transfer and expression of gene cassettes in avian cells. - Petropoulos, C J (1991)
We have constructed a series of replication-competent retrovirus vectors to introduce and express gene cassettes in avian cells. To characterize these vectors, we inserted the coding sequences for the bacterial chloramphenicol acetyltransferase (CAT) gene linked to the chicken beta-actin gene promoter or the mouse metallothionein 1 gene promoter. In all cases, we found the structure of integrated proviruses to be stable during serial cell passage in vitro. Chloramphenicol acetyltransferase activity was detected biochemically and immunocytochemically in infected cells. Cassettes were inserted in the vectors in the same or in the opposite orientation with respect to viral transcription. Although both orientations were functional, the cassettes inserted in the forward orientation were usually expressed at higher levels than the corresponding backward constructions. The level of expression was strongly influenced by surrounding proviral sequences, particularly by the transcriptional enhancer elements within the retrovirus long terminal repeat sequences. Expression was higher with vectors that contained the polymerase (pol) region of the Bryan high-titer strain of Rous sarcoma virus. Inclusion of the Bryan pol region also improved vector replication in the chemically transformed quail fibroblast line QT6.